Engineered T cells secreting αB7-H3-αCD3 bispecific engagers for enhanced anti-tumor activity against B7-H3 positive multiple myeloma: a novel therapeutic approach - Punchita Rujirachaivej; Teerapong Siriboonpiputtana; Kornkan Choomee; Kamonlapat Supimon; Thanich Sangsuwannukul; Pucharee Songprakhon; Krissada Natungnuy; Piriya Luangwattananun; Pornpimon Yuti; Mutita Junking; Pa-thai Yenchitsomanus (Journal of Translational Medicine)
Abstract Background Multiple myeloma (MM) is an incurable plasma cell malignancy with increasing global incidence. Chimeric antigen receptor (CAR) T-cell therapy targeting BCMA has shown efficacy in relapsed or refractory MM, but it faces resistance due to antigen loss and the tumor microenvironment. Bispecific T-cell engaging (BITE) antibodies also encounter clinical challenges, including short half-lives requiring continuous infusion and potential toxicities. Methods To address these issues, we developed a lentiviral system to engineer T cells that secrete αB7-H3-αCD3 bispecific engager molecules (αB7-H3-αCD3 ENG-T cells). We evaluated their effectiveness against MM cells with varying B7-H3 expression levels, from B7-H3neg to B7-H3high. Results The αB7-H3-αCD3 ENG-T cells demonstrated significant anti-tumor activity against MM cell lines expressing B7-H3. SupT-1 cells (B7-H3neg) served as controls and exhibited minimal cytotoxicity from αB7-H3-αCD3 ENG T cells. In contrast, these engineered T cells showed dose-dependent killing of B7-H3-expressing MM cells: NCI-H929 (B7-H3low), L-363 (B7-H3medium), and KMS-12-PE (B7-H3high). For NCI-H929 cells, cytotoxicity reached 38.5 ± 7.4% (p = 0.0212) and 54.0 ± 9.2% (p = 0.0317) at effector-to-target (E:T) ratios of 5:1 and 10:1, respectively. Against L-363 cells, cytotoxicity was 56.6 ± 3.2% (p < 0.0001) and 71.4 ± 5.2% (p = 0.0002) at E:T ratios of 5:1 and 10:1, respectively. For KMS-12-PE cells, significant cytotoxic effects were observed even at an E:T ratio of 1:1, with 27.2 ± 3.7% (p = 0.0004), 44.4 ± 3.7% (p < 0.0001), and 68.6 ± 9.2% (p = 0.0004) cytotoxicity at E:T ratios of 1:1, 5:1, and 10:1, respectively. Conclusions These results indicate that αB7-H3-αCD3 ENG T cells could be a promising therapy for B7-H3-positive MM. They may enhance current MM treatments and improve overall outcomes. Additional preclinical and clinical research is required to fully assess their therapeutic potential.